Conocimientos, actitudes y prácticas, relacionados a exposición solar y fotoprotección en el personal operativo de la Policía Nacional, del cantón Zamora. - Sinche Loarte, Karen Michelle (2018)
The ultraviolet radiation is the main environmental factor that alters the homeostasis of the skin as an organ, affecting the survival, proliferation and differentiation of several cell types and the light, is made up of visible light and ultraviolet and infrared radiation and exits the restlessness of That the emission levels of some lamps can be harmful to the skin and eyes. The general objective of this research was directed to know more about this knowledge, attitudes and practices related to solar exposure and photo protection in the operative staff of the National Police, Zamora Canton. Among the specific objectives are: to determine the knowledge on solar exposure and photo protection, to identify the attitudes towards the use of sunscreens and to establish daily practices, in front of solar exposure and photo protection. It was a descriptive, quantitative, perspective study. The universe and sample consisted of 144 participants and was carried out with the application of the pre-elaborated survey by Dr. Paredes Avalos Mijael, the same one that was adapted according to the local realities of our study. Obtaining the following results, 84.03 % a good knowledge about solar exposure and photo protection, 62.5 % of the police servers presented good attitudes, compared to the use of sunscreens and 80,56 % showed good practices. It is concluded that basic education and care in terms of solar exposure and adequate photo protection measures prevent thermal and ocular lesions throughout life. Key words: Ultraviolet solar radiation, solar protection, sunscreens, solar protection factor.